2014
DOI: 10.1364/josab.31.001730
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of photonic bandgap structure for a polaritonic photonic crystal in negative-index region

Abstract: A photonic bandgap (PBG) structure for a polaritonic photonic crystal (PPC) containing lithium tantalate (LiTaO 3 ) in the negative refractive index (NRI) region has been theoretically investigated. This region consists of a narrow frequency range of anomalous dispersion and a wide range of normal dispersion. The result shows that such PPC has a multiple-PBG structure with one gap located in the anomalous dispersion region and others in the normal dispersion region. PBG in the anomalous region is invariant wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Also we show regions where the omnidirectional band gaps emerges for specific generations of Octonacci photonic structure, except for TM waves. On the other hand, M.-R. Wu et al [44], have studied theoretically the photonic bandgap structure for a polaritonic photonic crystal containing lithium tantalate (LiTaO 3 ) in the NRI region. They have concluded that in NRI region we have a multi band gap structure and that the gap falling in the anomalous dispersion region can be treated as a zero-index gap which is further shown to be omnidirectional.…”
Section: Introductionmentioning
confidence: 99%
“…Also we show regions where the omnidirectional band gaps emerges for specific generations of Octonacci photonic structure, except for TM waves. On the other hand, M.-R. Wu et al [44], have studied theoretically the photonic bandgap structure for a polaritonic photonic crystal containing lithium tantalate (LiTaO 3 ) in the NRI region. They have concluded that in NRI region we have a multi band gap structure and that the gap falling in the anomalous dispersion region can be treated as a zero-index gap which is further shown to be omnidirectional.…”
Section: Introductionmentioning
confidence: 99%